2020
DOI: 10.31223/osf.io/jys47
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Small-scale capillary heterogeneity linked to rapid plume migration during CO2 storage

Abstract: Unpredicted, rapid plume elongation has been observed at subsurface CO2 storage projects worldwide, exemplified by the Sleipner project. We show that conventionally ignored centimetre-metre scale heterogeneity in capillary pressure characteristics can manifest as rapid field-scale, decametre-kilometre, plume migration. We analyse the effect in the Goldeneye Field, UK, a proposed storage site with a unique combination of sample/data accessibility and generality as an archetype sandstone reservoir. We overcome p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…Inasmuch as the previous work does not use direct measurement of multiphase flow properties from UNE sites, the assumption of immobile water is by itself not justified by these studies. Variability in multiphase flow properties within and between lithofacies and fracture systems affects the potentially time‐dependent redistribution of water or gas‐filled pathways—recent multiphase CO 2 sequestration fluid flow studies indicate centimeter‐to‐meter‐scale heterogeneity in capillary pressure affects rapid CO 2 plume migration (Jackson & Krevor, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Inasmuch as the previous work does not use direct measurement of multiphase flow properties from UNE sites, the assumption of immobile water is by itself not justified by these studies. Variability in multiphase flow properties within and between lithofacies and fracture systems affects the potentially time‐dependent redistribution of water or gas‐filled pathways—recent multiphase CO 2 sequestration fluid flow studies indicate centimeter‐to‐meter‐scale heterogeneity in capillary pressure affects rapid CO 2 plume migration (Jackson & Krevor, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…They have also shown that the CO 2 –brine system is sensitive to small‐scale heterogeneity in the capillary pressure characteristics of the rock. These, alongside modeling studies showing the upscaled impacts of small‐scale heterogeneity, show that the laboratory characterization of flow properties using approaches that incorporate the impacts of heterogeneity is key for accurate reservoir modeling (Gershenzon et al., 2017; Jackson & Krevor, 2020; Trevisan et al., 2017; Q. Zhou et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It is heterogeneity in multiphase flow characteristics that have a particularly significant impact when upscaled from submeter to field scales (Jackson & Krevor, 2020). Small‐scale heterogeneity in the pore structure results in variation in capillary pressure characteristics which results in saturation heterogeneity, and thus, relative permeability heterogeneity (Chaouche et al., 1994; Egermann & Lenormand, 2005; Huang et al., 1995; Krause & Benson, 2015; Krause et al., 2013; Perrin & Benson, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Heterogeneities in rock properties at the scales substantially amplify and complicate the effect of variations in pore-scale capillary forces, and are manifest in the large-scale saturation distributions within the current. Hence, in order to ensure safe and efficient sequestration, it is imperative to be able to model how small-scale heterogeneities, which are ubiquitous in all subsurface reservoirs, affect spreading rates at the macroscale (Jackson & Krevor 2020; Benham, Bickle & Neufeld 2021).…”
Section: Introductionmentioning
confidence: 99%
“…2013). Recently, Jackson & Krevor (2020) showed that small-scale capillary heterogeneities can significantly modify the large-scale migration of a buoyant plume within an aquifer. However, their numerical approach is both computationally intensive, and does not provide general scalings for different types of heterogeneity.…”
Section: Introductionmentioning
confidence: 99%